2020
DOI: 10.3390/cancers12030571
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Functionalized Magnetic Nanoparticles as a Nanocarrier of Photodynamic Anticancer Agent for Biomedical Theragnostics

Abstract: Various theragnostic agents have been devised and developed as cancer treatments; however, existing agents are often limited by their specific functions and complexities. Here, we report multifunctional magnetite (Fe3O4) nanoparticles functionalized with chlorin e6 (Ce6) and folic acid (FA) using a simple fabrication process to be used as theragnostic agents in photodynamic therapy (PDT). The effectiveness of cellular uptake of Fe3O4-Ce6-FA nanoparticles (FCF NPs) and its visualization as well as the photodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Briefly, MTT cell proliferation experiments showed that the cytotoxicity of PLA/DPPE-PEG-based TMX nanocapsule on MCF-7 breast cancer cell increased as compared with free tamoxifen and confirmed previous reports of nanodrug delivery (Kathle et al 2018;Nguyen et al 2008). The folate-decorated tamoxifen nanocapsule can increase cell uptake efficacy through FA receptormediated endocytosis in MCF-7 breast cancer cell line (Nam et al 2020). Accordingly, a comparison between the present study results and findings of our previous research revealed that the cytotoxic effect of loaded tamoxifen in folate-modified PLGA nanocapsules is approximately four times more than PLA/DPPE-PEG nanocapsules on MCF-7 cells.…”
Section: Cytotoxicity Analysis Of Tmx-loaded Pla/dppe-peg Nanocapsulessupporting
confidence: 86%
“…Briefly, MTT cell proliferation experiments showed that the cytotoxicity of PLA/DPPE-PEG-based TMX nanocapsule on MCF-7 breast cancer cell increased as compared with free tamoxifen and confirmed previous reports of nanodrug delivery (Kathle et al 2018;Nguyen et al 2008). The folate-decorated tamoxifen nanocapsule can increase cell uptake efficacy through FA receptormediated endocytosis in MCF-7 breast cancer cell line (Nam et al 2020). Accordingly, a comparison between the present study results and findings of our previous research revealed that the cytotoxic effect of loaded tamoxifen in folate-modified PLGA nanocapsules is approximately four times more than PLA/DPPE-PEG nanocapsules on MCF-7 cells.…”
Section: Cytotoxicity Analysis Of Tmx-loaded Pla/dppe-peg Nanocapsulessupporting
confidence: 86%
“…To evaluate the in vitro safety of L-929 cells, cytotoxicity tests were performed by previously reported method. 24 In brief, precultured cells with the same concentrations were cultured in 24-well plates for 1 day to test cellular uptake. The cells treated with Cu-MOF and NO⊂Cu-MOF (0, 12.5, 25, 50, 100, and 200 μg mL −1 ) were incubated for 1 day at 37 °C under air adjusted with 5% CO 2 in dark conditions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…117 Additionally, Ce6 and folic acid (FA) formulated IONPs can be used as a therapeutic tool in photodynamic therapy (PDT). 118 Recently, Yu and co-workers developed Ce6 loaded with PG functionalized IONPs linked with glucose, which can give both targeted photodynamic therapy and boost its immunogenicity in lung carcinoma. 119 Combining two therapies in one nanoparticle will increase its efficacy and decrease the side effects associated with it.…”
Section: Photodynamic Therapy (Pdt)mentioning
confidence: 99%